«
  
»
Usando a multiplicação, calcule:
a) (1+√5)² b) (2-√3)²


RESOLVENDO

Temos que:
\( (a+b)^2=a^2+2ab+b^2 \) e 
\( (a-b)^2=a^2-2ab+b^2 \)
Assim:
a) \( (1+\sqrt{5})^2=1^2+2\cdot1\cdot\sqrt{5}+(\sqrt{5})^2=1+2\sqrt{5}+5=6+2\sqrt{5} \) e 
b) \( (2-\sqrt{3})^2=2^2-2\cdot2\cdot\sqrt{3}+(\sqrt{3})^2=4-4\sqrt{3}+3=7-4\sqrt{3} \).

\( a) \\ (1 + \sqrt{5})^2 \\ \\ (1 + \sqrt{5}) * (1 + \sqrt{5}) \\ \\ 1 + 1* \sqrt{5} + 1* \sqrt{5} + 5 \\ \\ 6 + 2 \sqrt{5} \)
==========================================================
\( b) \\ (2 - \sqrt{3})^2 \\ \\ (2 - \sqrt{3}) * (2 - \sqrt{3}) \\ \\ 4 - 2 \sqrt{3} - 2 \sqrt{3} + 3 \\ \\ 7 -4 \sqrt{3} \)



TAREFAS SIMILARES: